Fan control and monitoring system using visual basic program - Khairul Hisyam Hasan (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2008)
This thesis is about the usage of a system to control and monitor a fan or more for certain kinds of operation and application in real life. This is including on how to control the fan speed manually or by using temperature sensor. The system also can be use to switch on and off the fan automatically by using timer settings.